Semantic Types of Personification in Design Advertising Texts (Proceedings of Southern Federal University. Philology, 2018)
Elena N. Lyashenko (Rostov-on-Don, Russian Federation)Personification is a way of artistic assimilation of reality, in the process of which an inanimate denotate is endowed with human properties. The formation of a new meaning is accompanied by implicit increments of an emotionally evaluative nature. The complex nature of this trail attracts the attention of linguists, literary critics, folklorists, psychologists, philosophers and culturologists. In the advertising sphere, personification performs various functions – the formation of an attractive image of the product, its individualization; demonstration of the advantages of the goods; creating a certain emotional mood. As instruments of impersonation in the analyzed texts are specific, collective and abstract nouns, as well as verbs with anthropomorphic semantics. In order to specify advertising images, goods are endowed with human attributes, they are represented as an assistant, friend, etc. The personifying semantics of verbal trademarks reflects the nature of the company’s activities.The idea of personification can be associated with the creation of contextual antonymic pairs, the playing of polysemantic words, the inclusion in the advertising text of the names of specific historical characters.Key words: personification, denotation of personification, human attributes, implicit information, individualization of the brand, formation of an attractive image of the product.